World Heart Federation Policy Brief: Front-Of-Pack Labelling: Unhealthy Changes in the Global Food System. Issue 1 (16th October 2020) - Champagne, Beatriz; Arora, Monika; ElSayed, Ahmed; Løgstrup, Susanne; Naidoo, Pamela; Shilton, Trevor; Vaca McGhie, Diana; Armstrong-Walenczak, Kelcey; Berteletti, Florence; Ganesan, Sandya; Popkin, Barry
On World Food Day, the World Heart Federation calls on governments to implement mandatory front-of-pack food labels. The World Heart Federation (WHF) has developed a new policy brief on front-of-pack labelling (FOPL) aimed at improving global standards on nutrition and creating healthy food environments. Poor diet is responsible for more deaths worldwide than any other risk factor, and is a leading cause of obesity, type 2 diabetes, and cardiovascular disease (CVD). Global estimates suggest that almost 2.3 billion children and adults are overweight. The growing availability of ultra-processed foods, which contain high levels of sugars, sodium, saturated fats and refined carbohydrates, is a key contributor to the current obesity epidemic, which is increasingly impacting low- and middle-income countries. The WHF Front-of-Pack Labelling Policy Brief highlights front-of-pack labelling as a way to create environments where consumers are able to make better informed, healthier food choices for themselves and their families. Currently, a wide variety of front-of-pack labelling systems have been implemented by governments and food manufacturers around the world, with varying levels of success. The new WHF Policy Brief provides evidence-based, practical guidance that can be adapted to local contexts. It highlights that in order the be implemented successfully, FOPL systems must take into account consumer literacy and prevailing cultural norms around food and nutrition. FOPL must be mandatory, government-led, and accompanied by broad public nutrition education initiatives. The WHF Policy Brief includes a set of policy recommendations to give governments the tools they need to select the FOPL system that will best meet the needs of their populations, including recommendations on how to develop an effective FOPL programme, how to implement it successfully, and how to monitor and evaluate outcomes.